2022
DOI: 10.3390/sports10120204
|View full text |Cite
|
Sign up to set email alerts
|

Knee Isokinetic Profiles and Reference Values of Professional Female Soccer Players

Abstract: Few studies have previously evaluated isokinetic parameters in female soccer players in comparison to those in males. The aim of this study was to describe normative quadriceps (Q) and hamstring (H) muscle strength values in professional female soccer players and to examine differences between dominant leg (DL) and nondominant leg (NDL). A standardized test protocol of concentric knee extension and flexion test protocol was conducted using the dynamometer isokinetic system (IsoMEd 2000). All the participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…One study compared Kin Com and Lido isokinetic machine and found no difference in muscle strength (Nm) between the Biodex and Lido for CON FLEX and CON EXT [43]. Isomed system was used in one study [4], and no ICC is available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study compared Kin Com and Lido isokinetic machine and found no difference in muscle strength (Nm) between the Biodex and Lido for CON FLEX and CON EXT [43]. Isomed system was used in one study [4], and no ICC is available.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [4,36,49] show a small negative D/ND ratio. This fact can be ex-plained by the presence of left sided players in the examined sample.…”
Section: Dominant/non Dominant Limb Ratiomentioning
confidence: 97%
“…Therefore, we can suggest that lower strength in women than in men may be one of the factors favoring an ACL injury. High levels of strength in the knee flexor/extensor musculature can prevent lower limb injuries in athletes, and specifically of the ACL [ 40 ], since the strength relationship between the quadriceps and ischiosural musculature is considered a relevant factor in the stability of the knee [ 41 , 42 , 43 ]. Therefore, an alteration of this musculature may increase the risk of lower limb injuries [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies [31,32,33] show a small negative D/ND ratio. This fact can be explained by the presence of left sided players in the examined sample.…”
Section: Methodsmentioning
confidence: 97%